The Influence of Herding Behavior and Confirmation Bias on Investment Decision in Generation Z with Gender as Moderating Variable: The Influence of Herding Behavior and Confirmation Bias on Investment Decision in Generation Z with Gender as Moderating Variable - Runtuwene, Maria Ester; Sibilang, Novie P (UNKLAB Business School, 2024)
In the digital era, access to investment information has become easier, especially through social media actively used by Generation Z. However, in making investment decisions, they can become more vulnerable to two biases known as herding behavior, which is the tendency to follow the actions of others, and confirmation bias, which is the tendency to seek information that reinforces their own views. This study aims to examine the influence of herding behavior and confirmation bias on investment decisions in Generation Z, with gender as a moderating factor. The population in this study is all Generation Z investors who are students of the Faculty of Economics and Business at Universitas Klabat, with sample selection using purposive sampling, resulting in 83 samples. The data used in this study is primary data, obtained from the distribution of questionnaires. This research uses linear regression to test the influence of research variables. The results of hypothesis testing indicate that herding behavior does not have a significant effect on the investment decisions of Generation Z, while confirmation bias has a significant effect. Additionally, gender does not moderate the relationship between herding behavior and investment decisions, nor between confirmation bias and investment decisions in Generation Z.